Conservation through education - Light, Marilyn H. S. (Lankesteriana: International Journal on Orchidology, 2016)
The way to conservation is through education. People of all ages everywhere are learning how to make wise use of natural resources to ultimately ben- efit and sustain future generations but clear goals, objectives and analogies are needed to reinforce the message. Conservation education initiatives can be compared to production of a food crop. A crop plant must first be selected to suit the growing environment then the fields prepared for planting. After planting, the growing plants must be cared for. Only after a successful harvest can the profit be realized.